Tinjauan Hukum dan Keamanan Penerapan E-Voting serta Terjaganya Asas-Asas Demokrasi dalam Pelaksanaan Pemilu di Indonesia - Andayani, Ana; Patanan, Elieser Andi; Lukman, Lukman (Innovative: Journal Of Social Science Research, 2024)
This article is titled "Legal and Security Review of E-Voting Implementation and Preservation of Democratic Principles in the Conduct of Elections in Indonesia." The research object is the application of e-voting technology in elections in Indonesia, focusing on legal aspects, data security, and the preservation of democratic principles. The aim of this research is to analyze the legal framework supporting e-voting, evaluate security challenges, and ensure that the principles of LUBER JURDIL democracy (direct, public, free, secret, honest, and fair) are upheld. The research uses a yuridis normative approach with a literature study technique, analyzing laws and regulations, official documents, and academic literature. The results indicate that while e-voting has the potential to enhance election efficiency and accessibility, its implementation faces legal and technical challenges. The absence of specific regulations regarding e-voting in Indonesia creates a legal gap, while security challenges such as data breaches and cyberattacks are key concerns. To ensure fairness and public trust, e-voting must adhere to democratic principles through transparent oversight mechanisms, robust data protection, and public education. Recommendations include strengthening election regulations, integrating technologies such as blockchain, and providing equitable infrastructure to ensure fair access for all voters.